Patient‐reported goal achievement following onabotulinumtoxinA treatment in patients with neurogenic detrusor overactivity. Issue 5 (6th April 2015) - Chartier‐Kastler, Emmanuel; Rovner, Eric; Hepp, Zsolt; Khalaf, Kristin; Ni, Quanhong; Chancellor, Michael
Abstract: Aims: To identify the self‐reported treatment goals of patients with urinary incontinence (UI) due to neurogenic detrusor overactivity (NDO), determine whether patients achieved their goals following onabotulinumtoxinA treatment, and assess impact of neurogenic disease (multiple sclerosis or spinal cord injury) and/or clean intermittent catheterization (CIC) on goal achievement. Methods: Data from two Phase III studies of onabotulinumtoxinA 200U (n = 227) or placebo (n = 241) in NDO patients (≥14 UI episodes/week; inadequately managed by anticholinergics) were pooled for analysis. At baseline, patients listed their top two qualitative treatment goals, which were distributed into eight subcategories. Six weeks post‐treatment, patients rated whether they achieved their goals (5‐point Likert scale). The frequency distribution of goals, the proportion of patients who achieved their goals, and goal achievement by etiology and use/non‐use of CIC were assessed. Results: At baseline, the most common goals were "be dry" (37.9%), "reduce other urinary symptoms" (26.4%), and "improve quality of life/sleep/emotions" (21.4%). Significantly higher proportions of onabotulinumtoxinA‐treated patients achieved their overall goals versus placebo (62.0% vs. 17.2%; P < 0.001). OnabotulinumtoxinA treatment resulted in higher goal achievement in all goal categories, regardless of etiology. CIC use did not negatively impact patients' overall goal achievement; significantly higher proportions of onabotulinumtoxinA‐treated patients versus placebo achieved their goals regardless of baseline catheterization use or de novo CIC during the first 6 weeks of the study. Conclusions: The majority of patients with UI due to NDO achieved their self‐determined treatment goals following onabotulinumtoxinA 200U therapy, regardless of etiology or CIC use. Neurourol. Urodynam. 35:595–600, 2016 . © 2015 The Authors. Neurourology and Urodynamics, published by Wiley Periodicals, Inc.